2015
DOI: 10.1186/s40173-015-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Did the Intergenerational Solidarity Pact increase the employment rate of older workers in Belgium? A macro-econometric evaluation

Abstract: In December 2005, the Belgian government adopted the law on the Intergenerational Solidarity Pact (ISP) aimed at increasing the employment rate of older workers. The main policies of the ISP consist of a pension bonus, reductions in employers' social security contributions and measures discouraging early retirement while encouraging working time reductions at the end of the career. We aim at evaluating the overall effectiveness of the ISP in raising the employment rate of older workers. To that purpose, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Changes to social security systems clearly induced prolonged labor force participation in recent decades, but they could not explain all recent increases in LFP/ERA. Studies that assessed increases in LFP in terms of changes to social security systems explained, at best, half of the increases [28], though most attributed 30% to 40% of the increases to such changes [15,19,20,29]. Four studies investigated the effect of factors not related to social security systems on increases in LFP/ERA.…”
Section: Authormentioning
confidence: 99%
“…Changes to social security systems clearly induced prolonged labor force participation in recent decades, but they could not explain all recent increases in LFP/ERA. Studies that assessed increases in LFP in terms of changes to social security systems explained, at best, half of the increases [28], though most attributed 30% to 40% of the increases to such changes [15,19,20,29]. Four studies investigated the effect of factors not related to social security systems on increases in LFP/ERA.…”
Section: Authormentioning
confidence: 99%
“…However, looking at the trends over the selected period, one observes a significant decrease in both unemployment exempted from job search and unemployment benefits with income supplement, while the number of people benefiting from a time-credit scheme increased. These recent trends confirm that public policies aim at discouraging early retirement while encouraging working-time reductions at the end of the career (Dejemeppe et al , 2015). However, one should remain cautious about this assertion as it has been shown that ‘participation in [a time-credit scheme] initially prolongs the time spent in employment (during the first two years for men and four years for women), but subsequently it accelerates the exit to early retirement’ (Albanese et al , 2015: 41).…”
Section: Contextual Background: From Early Retirement To Time Creditmentioning
confidence: 53%
“…The main policies of this pact «consist in a reduction in employers' social security contributions, several reforms intending to discourage access to early retirement, an easier access to working time reduction with (partial) wage compensation, and a pension bonus» (Dejemeppe et al, 2015, p. 2). Studies have shown in retrospect that these measures have not been very effective (Albanese, Cockx, 2015;Dejemeppe et al, 2015). Dejemeppe et al (2015) in particular conclude that these measures had very little impact on the employment rate for older workers, and that this has been to the detriment of younger workers.…”
Section: Retirement Agementioning
confidence: 99%
“…Studies have shown in retrospect that these measures have not been very effective (Albanese, Cockx, 2015;Dejemeppe et al, 2015). Dejemeppe et al (2015) in particular conclude that these measures had very little impact on the employment rate for older workers, and that this has been to the detriment of younger workers. Pension reform, in place since 2011, makes it more difficult to meet the conditions for early retirement (including tightening up on requirements in terms of age and length of career), career sabbaticals and so on.…”
Section: Retirement Agementioning
confidence: 99%